Structure and dynamics of water dangling OH bonds in hydrophobic hydration shells. Comparison of simulation and experiment - Tomlinson-Phillips, Jill; Davis, Joel; Ben-Amotz, Dor; Spångberg, Daniel; Pejov, Ljupčo; Hermansson, Kersti (American Chemical Society (ACS), 2011)
Molecular dynamics and electric field strength simulations are performed in order to quantify the structural, dynamic, and vibrational properties of non-H-bonded (dangling) OH groups in the hydration shell of neopentane, as well as in bulk water. The results are found to be in good agreement with the experimentally observed high-frequency (∼3660 cm(-1)) OH band arising from the hydration shell of neopentanol dissolved in HOD/D(2)O, obtained by analyzing variable concentration Raman spectra using multivariate curve resolution (Raman-MCR). The simulation results further indicate that hydration shell dangling OH groups preferentially point toward the central carbon atom of neopentane to a degree that increases with the lifetime of the dangling OH.